2007
DOI: 10.1007/s10900-007-9057-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart Disease Prevention Among Chinese Immigrants

Abstract: There is little information about the heart disease prevention behavior of Asian immigrants. Chinese are the largest Asian sub-group in the United States (US), and 69% of Chinese Americans are foreign-born. Our objective was to describe Chinese immigrants' heart disease prevention practices. A community-based, in-person survey of Chinese men and women was conducted in Seattle during 2005. Our study sample included 395 Chinese immigrants. Only 15% of the respondents consumed five or more servings of fruit/ vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 13 publications
2
40
1
Order By: Relevance
“…In the present study, we examined the associations between three acculturation measures and three health examination behaviors to provide a more comprehensive depiction of this relationship. Overall among the three Asian ethnic groups, greater acculturation was associated with a higher likelihood of having a routine physical exam, dental exam, and eye exam which is similar to findings from previous studies [4, 11, 28, 29]. This was particularly true when we used SL-ASIA or clusters as acculturation measures compared to length of stay.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, we examined the associations between three acculturation measures and three health examination behaviors to provide a more comprehensive depiction of this relationship. Overall among the three Asian ethnic groups, greater acculturation was associated with a higher likelihood of having a routine physical exam, dental exam, and eye exam which is similar to findings from previous studies [4, 11, 28, 29]. This was particularly true when we used SL-ASIA or clusters as acculturation measures compared to length of stay.…”
Section: Discussionsupporting
confidence: 86%
“…Although only a few studies have examined the relationship between acculturation and hypertension[5,7], the number of years living in the US has generally been an indicator for the risk of developing chronic diseases, including cardiovascular disease[25]. For example, among Chinese immigrants who moved to the US, recent immigrants reported a healthier diet and more physical activity compared with those who have resided in the US for more than 10 years[26]. Interestingly, however, Filipino Americans who lived in the US more than 30 years were not significantly different in their hypertension status compared with those who lived less than 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…(See Table 1. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) All papers were reviewed by one author (CG) and by one or more of the other authors, with coding disagreements resolved through discussion. Papers were reviewed against the STROBE Statement 22-item checklist for cross-sectional studies 33 to ensure they were adequately reported.…”
Section: Methodsmentioning
confidence: 99%
“…The nature of this relationship was the same and was found across various diverse ways of measuring acculturation and smoking, and using different statistical analytics and modeling. Five of the eight studies that used some aspect of language use or proficiency as an indicator of acculturation found a relationship 19,21,23,27,32 and three did not, 25,26,28 such that more use of English language was linked with less smoking for men 19,22,24,28,30,32 Both studies that distinguished between foreign-and North American-born found a relationship with smoking behaviour, 19,27 such that men born in China smoked more 27 and women born in China smoked less. 19,27 Of the studies that used multidimensional acculturation scales, 20,29,31,32 two studies, both in adolescents, did not find a relationship between scale scores and acculturation.…”
Section: Smoking Prevalencementioning
confidence: 97%
See 1 more Smart Citation